PENGARUH TINGKAT INVESTASI DAN ANGKATAN KERJA TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Munthe, Mario Nicolas (UNIKA Santo Thomas, 2018)
This study aims to determine the effect of investment and labor force on economic growth in Indonesia. The population in this study were all provinces in Indonesia as many as 33 provinces as well as being sampled with the 2011-20014 study period. The analytical model used is multiple linear regression with panel data and fixed effects models, but first performed a classic assumption test. The results of the study show that the level of investment and labor force partially have a positive and significant influence on economic growth. The most dominant variable affecting economic growth in Indonesia is employment